1996
DOI: 10.1046/j.1464-410x.1996.98619.x
|View full text |Cite
|
Sign up to set email alerts
|

A single positive prostate biopsy in six does not predict a low‐volume prostate tumour

Abstract: Objective To evaluate whether a single positive prostate biopsy in six systematic transrectal ultrasonography (TRUS)‐guided biopsies is predictive of a small tumour volume in a subsequent radical prostatectomy (RP) specimen. Patients and methods Of 158 patients submitted to RP for T1–T2 prostate cancer, 15.2% had one positive biopsy. The rate of positive margins (M+) and extracapsular involvement (C+) were assessed on the RP specimen in those with one positive biopsy (group I) and in those diagnosed by more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 5 publications
1
13
1
1
Order By: Relevance
“…2) suggested that approximately 12% of men with small-volume disease had positive surgical margins at radical prostatectomy (risk, 11.7%; 95% confidence interval, 8.3%-16.3%). Even when the definition was restricted further by a maximum Gleason score of 6, the proportion of patients with EPE ranged between 4% and 45% (median, 14%) 22,25,33 and between 7% 25 and 9% 22 of patients had positive margins.…”
Section: Findings In the Radical Prostatectomy Specimenmentioning
confidence: 99%
“…2) suggested that approximately 12% of men with small-volume disease had positive surgical margins at radical prostatectomy (risk, 11.7%; 95% confidence interval, 8.3%-16.3%). Even when the definition was restricted further by a maximum Gleason score of 6, the proportion of patients with EPE ranged between 4% and 45% (median, 14%) 22,25,33 and between 7% 25 and 9% 22 of patients had positive margins.…”
Section: Findings In the Radical Prostatectomy Specimenmentioning
confidence: 99%
“…We retrieved citations discussing histopathologic correlates of the subsequent RP specimen in patients undergoing surgery for 'insignificant' CaP on biopsy [2][3][4]11,[15][16][17][18][19] (Table 1). Definitions of 'insignificance' on biopsy varied between citations, from disease involving a single core 18 to disease of o0.5 mm total core length of Gleason sum p6. 17 Specific note was made of ultimate tumor volume within the gland in these cases as well as extracapsular extension (ECE) and frequency of positive surgical margins on subsequent RP specimens.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] These are the circumstances when decisions are made by physicians and patients with respect to therapy -specifically low risk therapy in many cases. If the construct of 'insignificance' on biopsy is not borne out on subsequent histopathologic examination, then low-risk therapy is less appropriate an option.…”
Section: Introductionmentioning
confidence: 99%
“…This ratio, however, was reduced to 10% by taking a second set of sextant biopsies. Ravery et al stressed the fact that a single positive biopsy in six does not predict a low-volume prostate cancer on an individual basis (138). Twenty-four radical prostatectomies were performed for prostate cancer detected with one positive biopsy out of six.…”
Section: Prediction Of Insignificant Diseasementioning
confidence: 99%